Analisis Morfometrik Siput Lola (Rochia nilotica L.) di Pulau Enggano, Bengkulu dan Pulau Sumbawa, Nusa Tenggara Barat - Risnita Tri Utami; Muhhamad Nasir; Ichtineza Halida Hardono; Dedi Pardiansyah; Teddy Triandiza; Asro Nurhabib (Journal of Marine Research, 2024)
Lola snails (Rochia nilotica L.) are economical marine biota that can be found in tropical coral reef areas spread across the Indo-Pacific region including Indonesia. However, over the past few decades it has been overexploited. Therefore, the purpose of this study was to determine the growth patterns and condition factors of lola snails in Bengkulu and West Nusa Tenggara waters. Data were collected in July-August 2024 in Enggano Island, Bengkulu and Pasaran Island and Kaung Island, West Nusa Tenggara using purpossive sampling method. The total number of lola snails obtained was 103 individuals with a diameter of 63.85-113.9 mm; height 67.7-113.22 mm' and weight 102-496 g. The length-weight relationship in Enggano Island, Bengkulu with a value of W = 0.000147L3.1947, Pasaran Island, NTB is W = 0.10649L 2.2378, and Kaung Island (NTB) with a value of W = 0.002221L2.6166.  The results of this study indicate that the growth pattern of lola snails on Enggano Island is a positive allometric model which means that weight growth is faster than height growth. While the growth pattern of lola snails on Pasaran Island and Kaung Island is a negative allometric model which means that height growth is faster than weight growth. The condition factor is 1.0048-1.0130, indicating that the Bengkulu and West Nusa Tenggara regions are still a suitable environment for the growth of lola snail.